1993
DOI: 10.1017/s0141347300017778
|View full text |Cite
|
Sign up to set email alerts
|

Body Dysmorphic Disorder: Phenomenology and Case Descriptions

Abstract: Thirteen cases of Body Dysmorphic Disorder (BDD) were described. There were eight males (61.5%) and five females (38.5%) with ages ranging from 16 to 37 (mean=24.7). All patients were also diagnosed as obsessive compulsive disorder (OCD), according to DSM-III-R, with the exception of one. Patients were administered the Yale Brown Obsessive Compulsive Scale, Beck Depression Inventory, Wechsler Intelligence Scale, Over-valued Ideation Scale and MMPI. The Phenomenology of BDD, its relationship to OCD, and the pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(25 citation statements)
references
References 12 publications
1
24
0
Order By: Relevance
“…However, it is interesting that both studies of BDD in adolescents found that most adolescents were female. This finding is consistent with several studies of adults with BDD in community and clinical settings (Rosen and Reiter, 1996;Veale et al, 1996;Faravelli et al, 1997), but differs from other adult BDD studies, which had a nearly equal gender ratio or contained more males than females (Hollander et al, 1993;Neziroglu and Yaryura-Tobias, 1993;Perugi et al, 1997;Phillips and Diaz, 1997;Bienvenu et al, 2000). It is unclear whether BDD actually affects more females than males-both adolescents and adults-or whether males with BDD are less likely to come to clinical attention or participate in a study such as ours, perhaps because it is more distressing and feels more shameful for males to reveal and discuss body image concerns.…”
Section: Discussionsupporting
confidence: 91%
“…However, it is interesting that both studies of BDD in adolescents found that most adolescents were female. This finding is consistent with several studies of adults with BDD in community and clinical settings (Rosen and Reiter, 1996;Veale et al, 1996;Faravelli et al, 1997), but differs from other adult BDD studies, which had a nearly equal gender ratio or contained more males than females (Hollander et al, 1993;Neziroglu and Yaryura-Tobias, 1993;Perugi et al, 1997;Phillips and Diaz, 1997;Bienvenu et al, 2000). It is unclear whether BDD actually affects more females than males-both adolescents and adults-or whether males with BDD are less likely to come to clinical attention or participate in a study such as ours, perhaps because it is more distressing and feels more shameful for males to reveal and discuss body image concerns.…”
Section: Discussionsupporting
confidence: 91%
“…Body dysmorphic disorder's gender ratio has also varied in clinical samples. Two previous BDD studies contained more women than men (72% of 82 subjects [17] and 76% of 50 subjects [45]), whereas 3 studies contained more men than women (62% of 13 subjects [50], 62% of 50 subjects [51], and 59% of 58 subjects [12]), and the largest previous study (n = 188) contained a nearly equal proportion of women (49%) and men (51%) [11]. The clinical studies contained samples of convenience and may therefore have various biases.…”
Section: Discussionmentioning
confidence: 99%
“…This is typical of the BDD population (Phillips, 1991;Neziroglu and Yaryura-Tobias, 1993a,b;Phillips et al, 1993). As is also common, all patients had repeatedly sought nonpsychiatric treatment with little or no relief (Neziroglu and Yaryura-Tobias, 1993a;Phillips et al, 1993) and all experienced secondary depression and anxiety (APA, 1994). Due to the similarities between the current sample and those described within the literature, results generated from this research appear to be applicable to the body dysmorphic population.…”
Section: Discussionmentioning
confidence: 99%
“…Any body part or several parts may be a source of concern. One, body part however, usually acquires prominence and arouses the most distress though focus may switch, to different features over the course of the disorder (Phillips, 1991;Neziroglu and Yaryura-Tobias, 1993a).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation